A Correlational Study of Social Media Content and Library Anxiety Among Users of Grhatama Pustaka - Ganggi, Roro Isyawati Permata; Ryandra, Erland (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study investigates the influence of content from the Instagram account @balaiyanpus.dpaddiy on the level of library anxiety among patrons of Grhatama Pustaka. The primary objective is to determine whether exposure to this social media content is associated with variations in users’ library anxiety levels. The Croatian Library Anxiety Scale (CRO-LAS) was employed as the measurement framework for assessing library anxiety. A quantitative correlational method was used, with data collected through questionnaires distributed to 100 respondents who follow the Instagram account. Simple random sampling was applied to select participants. Descriptive analysis shows that all indicators fall within the “excellent” category. Results from the Pearson Product–Moment correlation test reveal a strong negative correlation between Instagram content and library anxiety, with a correlation coefficient of –0.706, indicating that more positive engagement with the account is associated with lower levels of library anxiety. Furthermore, the coefficient of determination shows that 49.9% of the variance in library anxiety levels can be explained by the content of the @balaiyanpus.dpaddiy Instagram account. These findings suggest that informative and supportive social media content can play a significant role in reducing library anxiety among users.